The impact of vitamin d deficiency to treatment success of transforaminal epidural steroid injection - (:unkn) unknown (American Society of Interventional Pain Physicians, 2021)
Background: Transforaminal epidural steroid injection (TFESI) is an interventional technique used to relieve disc herniation related back and radicular pain. Although few studies have investigated the factors predicting positive outcomes after TFESI, there is no data concerning the possible relationship between pre-procedure serum 25-hydroxyvitamin D (25(OH)D) levels and the response to TFESI. Objectives: To investigate the effect of vitamin D deficiency to treatment success of fluoroscopy-guided transforaminal epidural steroid injection. Study Design: A retrospective assessment. Setting: A university hospital interventional pain management center. Methods: Nine hundred forty-eight patients received lumbosacral TFESI between January 2018 and December 2019 in a university hospital pain management center and were examined retrospectively for eligibility. Clinical and demographic data; magnetic resonance imaging (MRI); pre-procedure laboratory tests, including serum 25(OH)D; pain scores at baseline, third week, and third month follow-ups were collected. Results: A total of 83 patients were recruited and divided into 2 groups with respect to vitamin D status. The number of patients with serum 25(OH)D level below 20 ng/mL was 57 and the number of patients with serum 25(OH)D level above 20 ng/mL was 26. Treatment success rates were significantly lower in vitamin D deficient group at third week and third month (P: 0.006, P: 0.01). Limitations: Retrospective nature and the absence of functional outcomes. Conclusion: Vitamin D deficiency is associated with a lower probability of meaningful pain relief following TFESI. It may worth assessing serum vitamin D level prior to this intervention, although prospective investigation is necessary. © 2021, American Society of Interventional Pain Physicians. All rights reserved.
Keywords: Lumbar disc herniation; Transforaminal epidural steroid injection; Treatment success; Vitamin D deficiency